Analysis revealed the molecular mechanism of oxidative stress-autophagy-induced liver injury caused by high alkalinity: integrated whole hepatic transcriptome and metabolome - Shang, Xinchi; Geng, Longwu; Wei, Hai jun; Liu, Tianqi; Che, Xinghua; Li, Wang; Liu, Yuhao; Shi, Xiao dan; Li, Jianhong; Teng, Xiaohua; Xu, Wei (Frontiers in Immunology, 2024)
High-alkalinity water is a serious health hazard for fish and can cause oxidative stress and metabolic dysregulation in fish livers. However, the molecular mechanism of liver damage caused by high alkalinity in fish is unclear. In this study, 180 carp were randomly divided into a control (C) group and a high-alkalinity (A25) group and were cultured for 56 days. High-alkalinity-induced liver injury was analysed using histopathological, whole-transcriptome, and metabolomic analyses. Many autophagic bodies and abundant mitochondrial membrane damage were observed in the A25 group. High alkalinity decreased superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activity and the total antioxidant capacity (T-AOC) and increased the malondialdehyde (MDA) content in liver tissues, causing oxidative stress in the liver. Transcriptome analysis revealed 61 differentially expressed microRNAs (miRNAs) and 4008 differentially expressed mRNAs. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that mammalian target of rapamycin (mTOR), forkhead box O (FoxO), mitogen-activated protein kinase (MAPK), and the autophagy signalling pathway were the molecular mechanisms involved. High alkalinity causes oxidative stress and autophagy and results in autophagic damage in the liver. Bioinformatic predictions indicated that Unc-51 Like Kinase 2 (ULK2) was a potential target gene for miR-140-5p, demonstrating that high alkalinity triggered autophagy through the miR-140-5p-ULK2 axis. Metabolomic analysis revealed that the concentrations of cortisol 21-sulfate and beta-aminopropionitrile were significantly increased, while those of creatine and uracil were significantly decreased. The effects of high alkalinity on oxidative stress and autophagy injury in the liver were analysed using whole-transcriptome miRNA-mRNA networks and metabolomics approaches. Our study provides new insights into liver injury caused by highly alkaline water.